Molecular Cloning and Characterization of Sirtuin 1 and Its Potential Regulation of Lipid Metabolism and Antioxidant Response in Largemouth Bass (Micropterus salmoides) - Huang, Yuting; Wang, Shilin; Meng, Xiaoxue; Chen, Naisong; Li, Songlin (Frontiers in Physiology, 2021)
Sirtuin 1 (SIRT1) of largemouth bass (Micropterus salmoides) was cloned and characterized in the present study and the influence of SIRT1 activation induced by resveratrol inclusion on the expression of genes related to lipid metabolism and antioxidation were also investigated. The SIRT1 of largemouth bass, with full-length cDNA sequence of 3395 bp encoding 695 amino acids, was mainly expressed in gonad, heart and liver. The analysis of multiple sequence alignment revealed that, in accordance with other species, SIRT1 of largemouth bass contained highly conserved substrate binding site and NAD+ binding site. The result of subcellular localization displayed that SIRT1 of largemouth bass was mainly localized in the nucleus. The inclusion of 1.0 and 2.5 ‰ dietary resveratrol, a natural SIRT1 activator, significantly elevated the SIRT1 protein expression. Meanwhile, the phosphorylation of AKT1 and FoxO1 followed similar pattern with that of SIRT1, indicating the activation of insulin pathway, which may result in the inhibition of lipogenesis and activation of lipolysis, and reduced hepatic triglycerides content. Additionally, the activation of SIRT1 induced by dietary resveratrol elevated the antioxidant capacity at both transcriptional level and enzymatic level, which was probably mediated by the transcription factor Nrf2. In above, SIRT1 was suggested to be involved in improving antioxidant capacity and alleviating hepatic lipid deposition in largemouth bass.